2019
DOI: 10.3389/fimmu.2019.01152
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Telomere Integrity and DNA Repair Machineries by KML001 Induces T Cell Senescence, Apoptosis, and Cellular Dysfunctions

Abstract: T cells in chronic viral infections are featured by premature aging with accelerated telomere erosion, but the mechanisms underlying telomere attrition remain unclear. Here, we employed human CD4 T cells treated with KML001 (a telomere-targeting drug) as a model to investigate the role of telomere integrity in remodeling T cell senescence. We demonstrated that KML001 could inhibit cell proliferation, cytokine production, and promote apoptosis via disrupting telomere integrity and DNA repair machineries. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 62 publications
6
43
0
Order By: Relevance
“…These results indicate that ICRF-193-induced, Top2α-mediated topological DDR involves dynamic activation and depletion of ATM. These are in line with our recent findings of ATM dynamics in healthy CD4 T cells treated with KML001 or Top1 inhibitor 8,9 and in CD4 T cells derived from patients with chronic HCV and/or HIV infection [5][6][7] .…”
Section: Top2α-mediated Topological Ddr Involves Dynamic Activation Asupporting
confidence: 92%
See 4 more Smart Citations
“…These results indicate that ICRF-193-induced, Top2α-mediated topological DDR involves dynamic activation and depletion of ATM. These are in line with our recent findings of ATM dynamics in healthy CD4 T cells treated with KML001 or Top1 inhibitor 8,9 and in CD4 T cells derived from patients with chronic HCV and/or HIV infection [5][6][7] .…”
Section: Top2α-mediated Topological Ddr Involves Dynamic Activation Asupporting
confidence: 92%
“…During chronic viral infections, however, T cells are always dysregulated and often non-responsive to vaccines 1 . We and others have previously reported that T cells from chronically virusinfected individuals are prematurely aged due to accelerated telomere erosion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , but the underlying mechanisms for T cell telomeric DNA damage remain unclear. Since Top2α is required to remove DNA supercoiling generated during cell proliferation, and Top2cc can become trapped during gene transcription to cause Top2cc-linked PDB due to TDP2 depletion 21,22 , we hypothesized that DNA topology in T cells may be affected during viral infections to trigger DDR as a mechanism of virus-induced immune evasion, and thus, persistent infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations